Instructional Leadership of Teachers - ทวีโชติ, จิรวดี; ฉลากบาง, วัลนิกา (Journal of Roi Et Rajabhat University, 2018)
Several challenges had been recognized in the implementation of instructional management. The few examples were student-related issues concerning cognitive domain, affective domain and psychomotor domain, teacher-related issues on readiness to teach, knowledge, teaching techniques, instructional technology skills, instructional innovation or teaching model application, and assessment and evaluation. To address these challenges, teachers were expected to possess instructional leadership, which comprised certain behaviors that could be divided into 5 factors, namely instructional skill and ability, the understanding and ability in curriculum development, evaluation and assessment, self-and-peer-teacher development and transformational leadership. Teachers with instructional leadership needed to create and initiate positive changes in schools and communities, conduct their duties in accordance with their role and profession, strive towards self-improvement to tackle with rapid changes and be an experienced classroom manager, which would enable teachers to provide efficient learning activities that would eventually lead to better educational improvement.